Canadian Stroke Best Practice Consensus Statement: Acute Stroke Management during pregnancy. Issue 7 (October 2018) - Ladhani, Noor Niyar N; Swartz, Richard H; Foley, Norine; Nerenberg, Kara; Smith, Eric E; Gubitz, Gord; Dowlatshahi, Dariush; Potts, Jayson; Ray, Joel G; Barrett, Jon; Bushnell, Cheryl; Bal, Simerpreet; et al.
The Canadian Stroke Best Practice Consensus Statement Acut e Stroke Management during Pregnancy is the second of a two-part series devoted to stroke in pregnancy. The first part focused on the unique aspects of secondary stroke prevention in a woman with a prior history of stroke who is, or is planning to become, pregnant. This document focuses on the management of a woman who experiences an acute stroke during pregnancy. This consensus statement was developed in recognition of the need for a specifically tailored approach to the management of this group of patients in the absence of any broad-based, stroke-specific guidelines or consensus statements, which do not exist currently. The foundation for the development of this document was the concept that maternal health is vital for fetal well-being; therefore, management decisions should be based first on the confluence of two clinical considerations: (a) decisions that would be made if the patient wasn't pregnant and (b) decisions that would be made if the patient hadn't had a stroke, then nuanced as needed. While empirical research in this area is limited, this consensus document is based on the best available literature and guided by expert consensus. Issues addressed in this document include initial emergency management, diagnostic imaging, acute stroke treatment, the management of hemorrhagic stroke, anesthetic management, post stroke management for women with a stroke in pregnancy, intrapartum considerations, and postpartum management. These statements are appropriate for healthcare professionals across all disciplines and system planners to ensure pregnant women who experience a stroke have timely access to both expert neurological and obstetric care.